Appearance concerns among women with neurofibromatosis: examining sexual/bodily and social self‐consciousness. Issue 12 (19th July 2013) - Smith, Kelly B.; Wang, Daphne L.; Plotkin, Scott R.; Park, Elyse R.
Abstract Objective Neurofibromatosis (NF) 1 and 2 have distinct appearance effects, yet little research has examined patients' appearance concerns. We assessed appearance concerns and self‐consciousness, self‐esteem, and loneliness among women with NF. Methods Women with NF1 (n = 79) and NF2 (n = 48) completed the Derriford Appearance Scale to assess appearance concerns and sexual/bodily and social self‐consciousness, Rosenberg Self‐Esteem Scale, and UCLA Loneliness Scale. Women's appearance concerns were coded to determine whether they were NF‐related and whether psychosocial factors contributed to the concerns. Results A total of 85% of women reported appearance concerns, many of which were NF‐related and attributed to psychosocial factors. Women with NF1 reported significantly more sexual/bodily self‐consciousness but similar levels of social self‐consciousness compared with women with NF2. Significantly higher sexual/bodily self‐consciousness was found among married/cohabiting women regardless of NF group. Compared with general population norms and breast cancer survivors (BCS), women with NF1 reported significantly greater sexual/bodily and social self‐consciousness. Women with NF2 reported less sexual/bodily self‐consciousness compared with population norms, yet tended to report greater sexual/bodily self‐consciousness than BCS. Women with NF2 reported significantly greater social self‐consciousness compared with population norms and BCS. For both NF1 and NF2, higher levels of sexual/bodily and social self‐consciousness were related to lower self‐esteem and higher levels of social self‐consciousness to more loneliness. Conclusions Appearance concerns are prevalent, and social self‐consciousness is high, among women with NF1 and NF2. Women with NF1 compared with NF2 experience more sexual/bodily self‐consciousness. Providers should assess the impact of NF on women's self‐perceptions and address sexual, body image, and social concerns. Copyright © 2013 John Wiley & Sons, Ltd.